2013
DOI: 10.1007/s10067-013-2320-5
|View full text |Cite
|
Sign up to set email alerts
|

High disease activity is related to low levels of physical activity in patients with ankylosing spondylitis

Abstract: This study aims to compare physical activity (PA) level and exercise habits in patients with ankylosing spondylitis (AS) who have high disease activity with those who have low disease activity and, further, to compare both groups with population controls. Cross-sectional study design was used. The participants include 149 patients (mean age 49.3 (SD 11.1), 61% men, 54% high disease activity) and 133 controls (mean age 52.7 (SD11.3), 58% men). PA was reported with the International PA Questionnaire-Long and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
2
32
2
3
Order By: Relevance
“…disease activity, severity, or treatment, or to patient-related characteristics? Whether the level of physical activity is related to disease activity is uncertain, some studies finding no correlation38 ) , others reporting that patients with high disease activity exercised less39, 40 ) or reversely, more41 ) . Furthermore, other factors such as patients’ willingness and motivations to exercise may be more important to explain physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…disease activity, severity, or treatment, or to patient-related characteristics? Whether the level of physical activity is related to disease activity is uncertain, some studies finding no correlation38 ) , others reporting that patients with high disease activity exercised less39, 40 ) or reversely, more41 ) . Furthermore, other factors such as patients’ willingness and motivations to exercise may be more important to explain physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, pain was also frequently reported as a barrier in our study. Studies have demonstrated that a large proportion of patients with AS are less physically active than is recommended for health promotion (Fongen et al, ; Haglund et al, ; Passalent et al, ; Santos et al, ; Sundstrom et al, ; Swinnen et al, ; Uhrin et al, ). This indicates that patients with AS cannot simply be given general physical activity recommendations; they also need advice from health professionals with the necessary knowledge about physical activity and disease pathology in order to overcome the disease‐related barriers to physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise should be part of disease management through the course of the disease and may have beneficial effects on spinal mobility, physical function, general well‐being, pain and disability (Dagfinrud et al, ; van den Berg et al, ). Despite this, studies have demonstrated that a large proportion of patients with AS are less physically active than recommended (Fongen et al, ; Haglund et al, ; Passalent et al, ; Santos et al, ; Sundstrom et al, ; Swinnen et al, ; Uhrin et al, ), so more knowledge about factors that influence participation is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Des études cas-témoin montrent certes que la consommation maximale en oxygène à l'effort exprimée en moyenne est diminuée chez les patients atteints de spondyloarthrite comparativement aux témoins indemnes [5,6]. La diminution de l'activité physique attendue en conséquence chez ces patients n'est en revanche qu'inconstamment retrouvée [7][8][9][10]. Dans l'étude la plus vaste, regroupant plus de 2000 patients sué-dois, les deux tiers avaient une activité physique en accord avec les recommandations de l'Organisation mondiale pour la santé, et le risque standardisé d'activité physique était de 1,09 (IC95 1,04-1,15), indiquant un niveau d'activité physique légèrement supérieur à celui observé dans la population générale [8].…”
Section: Prérequisunclassified